2019
DOI: 10.1016/j.physletb.2019.07.026
|View full text |Cite
|
Sign up to set email alerts
|

No hair theorem for bound-state massless static scalar fields outside horizonless Neumann compact stars

Abstract: We study no-hair theorem for horizonless objects, being subject to Neumann boundary conditions. For massive scalar fields, a no hair theorem for Neumann compact stars was proved by us in a previous paper, where the nonzero scalar field mass condition is essential in the proof. In the present work, for massless scalar fields, we prove a no hair theorem, which claims that bound-state massless static scalar fields cannot exist outside asymptotically flat horizonless neutral Neumann compact stars.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…With fieldcurvature couplings, such no hair theorem could also hold in the horizonless gravity [38][39][40]. Moreover, we proved no hair theorem for horizonless compact stars with other boundary conditions [41][42][43].…”
Section: Introductionmentioning
confidence: 76%
“…With fieldcurvature couplings, such no hair theorem could also hold in the horizonless gravity [38][39][40]. Moreover, we proved no hair theorem for horizonless compact stars with other boundary conditions [41][42][43].…”
Section: Introductionmentioning
confidence: 76%
“…With a nonzero cosmological constant, such no static scalar hair theorem still holds for horizonless neutral reflecting compact stars [30][31][32]. When considering charged horizonless reflecting compact stars, static scalar fields cannot exist outside stars of large size and in contrast, static scalar hair can form outside charged horizonless reflecting compact stars with small radii [33]- [37]. Very differently, if we want to obtain static scalar hair outside asymptotic flat charged black holes, we usually have to put the black hole in a box [38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Large charged reflecting stars also cannot support static scalar field hairs [37][38][39][40][41][42][43][44]. Moreover, it was found that scalar fields cannot exist outside compact stars with Neumann surface boundary conditions [45,46].…”
Section: Introductionmentioning
confidence: 99%